The arguments against G8 / edited by Gill Hubbard and David Miller. - Hubbard, Gill; Miller, David, 1964- (Pluto, 2005)
Every year world leaders convene for their annual G8 conference, accompanied by thousands of protesters and anti-globalization activists. This text provides a guide for anyone who want to know more about the G8, what it is, and why it's a problem.